THE EFFECTS OF THE LEAD ON THE SEED GERMINATION, ROOT GROWTH, AND ROOT TIP CELL MITOTIC DIVISONS OF LENS CULINARIS MEDIK - Kiran, Yasar; Sahin, Ahmet (Gazi Univ, 2005)
In this study, the effects of lead (PbCl2) one of the significant environmental pollutant, on seed germination, root growth and mitotic divisions of the root tip cells of lentil (Lens culinaris Medik.) were investigated. Different concentrations (0.125, 0.250, 0.500 and 1.000 mM Pb+2) of lead were applied. It was observed that there are no significant differences in the germination of seeds that exposed to low lead concentrations. On the other hand, at higher concentrations of lead inhibited germination. In addition, root growth was inhibited according to the control group at all concentrations. In parallel to the increase of the lead concentrations cell division was decreased, several mitotic anomalies such as cmitosis, lagging chromosomes, multipolar anaphases and Chromosome bridges were increased.
Keywords: Lead; Lens culinaris; germination; mitosis; heavy metals